2008
DOI: 10.1111/j.1949-3606.2008.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Antonak and Harth's Mental Retardation Attitude Inventory for Kuwait's Culture

Abstract: The purpose of this research was to adapt Antonak and Harth's (1994) Mental Retardation Attitudes Inventory for the Kuwaiti culture and to investigate its four‐dimensional structure. The study also aimed at identifying a unidimensional subset of items besides examining the quality of the identified items and the overall inventory. The 34 ‐item adapted inventor y was administered to 56 4 college students. Item analysis indicated that 29 items have had good psychometric characteristics. However, the exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Commonly, persons with a disability are regarded as burdensome and shameful, because they are incapable of contributing to traditional social obligations and roles (Kandari and Salih 2008). As long as such traditional beliefs persist, the present study expects that, with lack of family services, Kuwaiti mothers will continue to believe that they cannot deal with the stress at home, talk with friends and family about their child, or ask others for help.…”
Section: Introductionmentioning
confidence: 86%
“…Commonly, persons with a disability are regarded as burdensome and shameful, because they are incapable of contributing to traditional social obligations and roles (Kandari and Salih 2008). As long as such traditional beliefs persist, the present study expects that, with lack of family services, Kuwaiti mothers will continue to believe that they cannot deal with the stress at home, talk with friends and family about their child, or ask others for help.…”
Section: Introductionmentioning
confidence: 86%
“…Also, Pettigrew and Troop (2000) stated that 94% of the 203 studies about contact and attitudes indicated an inverse relationship between face-to-face contact and negative attitudes. Although some Eastern studies that were conducted in China (e.g., Siperstein et al, 2011;Wong, 2008), Kuwait (e.g., Salih & Al-Kandari, 2007;Al-Kandari & Salih, 2008), and Japan (e.g., Horner-Johnson et al, 2002) found a small effect of contact between students with and without IDD in changing students' attitudes towards inclusion, other studies (e.g., Chadsey, 2004;Siperstein et al, 2007) suggested that if students have limited opportunities to interact with a peer with IDD in the educational setting, their attitudes towards inclusion will remain negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, studies in Arab societies (e.g., Mohammed, 1995;Rahal, 2005;Saratawey, 1990, conducted in Bahrain, Syria, and Egypt, respectively) focused on attitudes in association with variables, such as type of disabilities (e.g., physical, hearing, intellectual, and vision impairments), television programs, academic performance, nationality, the visibility of disability, educational status, and specialisation. Meanwhile, studies conducted in Kuwait (Al-Kandari & Salih, 2008;Salih & Al-Kandari, 2007) focused on identifying the attitudes of college students towards the integration of people with IDD in mainstream society.…”
Section: Rationale For the Studymentioning
confidence: 99%
See 2 more Smart Citations